Boé e concreto Contra-Flecha : o cerrado e a floresta na construção de uma dramaturgia mestiça - Lana, Wanderson Alex Moreira de (2021)
This research analyzes the dramaturgy of the stage plays Boé (2014) by Primavera do Leste’s Teatro Faces and “concreto CONTRA- FLECHA” (2017) by Alta Floresta’s Teatro Experimental, taking into account how the cerrado (Brazilian Savanna) and the Amazon Rainforest not only impact the works’ aesthetics of these groups, but also put in evidence a group organization policy and influence the interest in debating aspects related to the colonization process in the (Brazilian) state of Mato Grosso starting in the 20th Century.Teatro Faces is the first theater group in the city of Primavera do Leste (southeast/cerrado) to be organized as a local cultural institution. This is also true for Alta Floresta’s Teatro Experimental (north/Mato Grosso Amazon Rainforest) founded in the 1980s. Respectively, the groups count with 15 and 32 years since their foundation and their productions are profoundly rooted in their geographical location. Cerrado and the Amazon Rainforest impact in a very particular way the methodology of the theater groups’ scenic montages, the ways in which they exist and move the scenic arts in Mato Grosso’s inland areas. Through Boé, a stage play that abandons the centrality of the text and embraces performativity and the concept of expanded dramaturgy, and “concreto CONTRA-FLECHA”, which uses memory as a conducting wire to think about territory, it is possible to perceive the relationships that both groups keep with colonization aspects and the fight against these colonial roots (MIGNOLO, 2010, 2017; QUIJANO 2005, 2010). Intertwined by the concepts of place and non-place (Marc Augé, 1994) – as well as the concepts of space, territory, territoriality, and the idea of space-time (HAESBART, 2002; SANTOS, 2014), and the concepts of mixture and its consequences (GLISSANT, 2005; GRUZINSKI, 2001; PINHEIRO, 2020) – stage plays of Primavera do Leste’s Teatro Faces and Alta Floresta’s Teatro Experimental characterize a deterritorialized and territorialized dramaturgy, political, decolonial, therefore, a Mestizo Dramaturgy.